Salt-influenced normal fault growth and forced folding; the Stavanger Fault System, North Sea - Lewis,MM; Jackson,CAL; Gawthorpe,RL (Journal of Structural Geology, 2013)
Displacement ratio (Dr) is the ratio of salt thickness (Tv) to sub-salt normal fault displacement (D) (Dr = Tv /D), and it is typically used to predict the degree of geometric and kinematic linkage between sub- and supra-salt fault populations, and the overall resultant structural style in salt-influenced extensional settings. However, we currently lack natural examples of how Dr and the underlying geological controls vary, and how these may control the three-dimensional geometry and evolution of salt-influenced normal fault systems. Furthermore, it is currently unknown if kinematic coherence in salt-influenced extensional settings can be maintained over long length-scales (101-103 m) and for long periods of extension, and how this may impact the growth and geometry of large-throw (> 500 m), salt-influenced normal fault systems. In this paper we use a 3600 km2, high-quality 3D seismic reflection dataset and borehole data from the Stavanger Fault System (SFS), Egersund Basin, eastern North Sea Basin to investigate; (i) how pre-rift salt thickness (Tv) and sub-salt fault throw (T) control the structural style and evolution of a basin-bounding, salt-influenced normal fault system; and (ii) the role salt plays in maintaining kinematic coherence in normal fault systems. We demonstrate that; (i) pre-rift salt distribution (Tv), specifically its presence in the proto-footwall (i.e., when Tv > 0), is the primary control on partitioning of faulting and (forced) folding along the fault system, and the style of linkage (i.e., hard- or soft-linkage) between sub- and supra-salt fault populations; and (ii) that sub- and supra-salt fault populations represent brittle elements of single geometrically and kinematically coherent structure, which is related to the ductile translation of strain on a scale (up to 8 km) and duration (c. 65 Myr) that is significantly greater than previously documented.